All things to all people? The provision of outreach by community mental health teams for older people in England: findings from a national survey. (3rd October 2013) - Tucker, Sue; Wilberforce, Mark; Brand, Christian; Abendstern, Michele; Challis, David
<x xml:space="preserve">Abstract</x> Objective The objective of this study is to identify the extent of outreach activity community mental health teams (CMHTs) for older people provide to mainstream services in light of the recommendations of the National Dementia Strategy. In particular, to determine the range of settings in receipt of support; to specify the form of this activity; to identify the professionals involved; and to explore the factors associated with the provision of such support. Methods A self‐administered postal questionnaire was sent to all CMHTs in England. The reported arrangements were categorised and reviewed according to a taxonomy of outreach developed from the literature. Results Three hundred and seventy six (88%) of the CMHTs responded. Although nearly all teams undertook some outreach work, much of this was informal in nature. Nevertheless, the vast majority of teams had some formal outreach arrangements in at least one mainstream setting. Just less than three‐quarters provided support (most typically education) to care homes, approaching half centres to day centres, and over a third to primary care practices, social services teams, home care providers and general hospitals, respectively. Link workers were the favoured means of supporting general hospital staff. Community mental health nurses were most commonly involved in providing outreach, and larger teams were more likely than smaller teams to have formalised arrangements. A significant minority of teams expressed concerns about their capacity to provide effective services. Conclusions The findings suggest that both more resources and more evidence will be needed to meet the National Dementia Strategy's aim of improving care for older people with mental health problems in mainstream settings. Copyright © 2013 John Wiley & Sons, Ltd.